Money or honor ; A domestic problem ; On our own [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
The secretary of Energy's pronouncement that the government was considering a settlement agreement with Westinghouse ; the maker of Bataan Nuclear Power Plant. Enactment of "Maids bill" by Congress gives housewives open complaint about the deteriorating quality for household helpers. McKintosh Production on Les Miserables staged in the Philippines by Filipino performers.